The effect of co-ordination and balance on developing some basics skills for age catogaries in soccer - Aubbas, Mofq (Journal of Physical Education, 2010)
The research research consist five chapters, The lst chapter contain The definatain, The problem, aims, hybotheas and finally The rields.The 2nd chapter cantinas The Thero tical stdies, which knowing The Balancing and corridnation brills and now to useit in developing basic skills in soccer Then The researcher Takes The Basic skills especially controlling and bribling drills. The third chapter include research method and field process.The sample of research was from soccer school That belong to Iraqi soccer federation also The pilot study was heild and The post Test Then The main expierment. The fourth chapter consist display and anallzing research results which received and knowing dereloping of Basic skills .cast The fifth chapter contains conclusions and recommendation, also The Research contains guestionary and several attachs and paper of resources